MYCN and HDAC2 cooperate to repress miR-183 signaling in neuroblastoma - Lodrini, Marco; Oehme, Ina; Schröder, Christina; Milde, Till; Schier, Marie Catherine; Kopp-Schneider, Annette; Schulte, Johannes H.; Fischer, Matthias; De Preter, Katleen; Pattyn, Filip; Castoldi, Mirco; Muckenthaler, Martina; et al. (Nucleic acids research, 2013)
MYCN is a master regulator controlling many processes necessary for tumor cell survival. Here, we unravel a microRNA network that causes tumor suppressive effects in MYCN-amplified neuroblastoma cells. In profiling studies, histone deacetylase (HDAC) inhibitor treatment most strongly induced miR-183. Enforced miR-183 expression triggered apoptosis, and inhibited anchorage-independent colony formation in vitro and xenograft growth in mice. Furthermore, the mechanism of miR-183 induction was found to contribute to the cell death phenotype induced by HDAC inhibitors. Experiments to identify the HDAC(s) involved in miR-183 transcriptional regulation showed that HDAC2 depletion induced miR-183. HDAC2 overexpression reduced miR-183 levels and counteracted the induction caused by HDAC2 depletion or HDAC inhibitor treatment. MYCN was found to recruit HDAC2 in the same complexes to the miR-183 promoter, and HDAC2 depletion enhanced promoter-associated histone H4 pan-acetylation, suggesting epigenetic changes preceded transcriptional activation. These data reveal miR-183 tumor suppressive properties in neuroblastoma that are jointly repressed by MYCN and HDAC2, and suggest a novel way to bypass MYCN function.